2021
DOI: 10.1016/j.clon.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Keep Calm and Carry on: Safety, Feasibility and Early Outcomes of Head and Neck Cancer Treatment During the COVID-19 Pandemic

Abstract: Madam d Evaluating outcomes in patients treated during the first wave of the COVID-19 pandemic is paramount to developing future evidence-based practice.In early 2020 patients with cancer were thought to be particularly vulnerable to and that anti-cancer treatments may further increase that risk [2e4]. Guidance was issued on the modification of standard treatments for head and neck cancer (HNC) [5e10].We completed a retrospective cohort study of all patients with HNC treated in our UK tertiary level oncology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is possible that rates of advanced disease will rise given the well-documented issues of limited access to health services and reported lower rates of diagnosis generally; however, emerging research from European countries has not demonstrated this. 37 While HNC services have been able to continue diagnosing and treating patients throughout the COVID-19 pandemic, 38 there is concern that the pandemic may have led to more patients presenting with advanced disease, or not at all, to health services. It will be important to monitor the impact of the COVID-19 pandemic on the incidence of advanced-stage HNC and we have shown there is improving data available via the UK cancer registries which can be used to monitor this and inform service recovery.…”
Section: Fig 3 Hnc Incidence Counts and Rates By Stage At Diagnosis F...mentioning
confidence: 99%
“…It is possible that rates of advanced disease will rise given the well-documented issues of limited access to health services and reported lower rates of diagnosis generally; however, emerging research from European countries has not demonstrated this. 37 While HNC services have been able to continue diagnosing and treating patients throughout the COVID-19 pandemic, 38 there is concern that the pandemic may have led to more patients presenting with advanced disease, or not at all, to health services. It will be important to monitor the impact of the COVID-19 pandemic on the incidence of advanced-stage HNC and we have shown there is improving data available via the UK cancer registries which can be used to monitor this and inform service recovery.…”
Section: Fig 3 Hnc Incidence Counts and Rates By Stage At Diagnosis F...mentioning
confidence: 99%